PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DENGAN MENGGUNAKAN METODE IMPORTANCE PERFOMANCE ANALYSIS (Studi Pada Pelanggan Bus Trans Metro Pekanbaru, Koridor III Rute Uin Panam-MTQ). - Lina Lestari; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in Trans Metro Pekanbaru, located on Jl. Gatot Subroto, Rintis, Lima Puluh, Pekanbaru City, Riau. The problem in this study is the occurrence of customer fluctuations that are thought to be influenced by customer satisfaction. The purpose of this study was to determine the effect of service quality on customer satisfaction using the importance performance analysis method (a study of Trans Metro Pekanbaru bus customers, Corridor III of the Uin Panam- MTQ Route). Samples were taken based on the method using Slovin formula, amounting to 100 respondents. Hypothesis testing uses simple linear regression analysis method and Importance Performance Analysis analysis with the results showing that service quality significantly influences customer satisfaction on Trans Metro Pekanbaru. With a simple linear regression calculation of 0.333. While the importance performance analysis for service quality obtained 4 service attributes whose suitability value is still below 77.60%. Whereas for customer satisfaction, 5 attributes were obtained whose conformity values were still below 83.63%. This shows that the average number for each dimension has been determined. Even though in reality there are still attribute items whose suitability values indicate interest> assessment level or it can be said that expectations> performance, so it needs to be prioritized its improvement. Keywords : Service Quality, Customer Satisfaction, Importance Performance Analysis.